68.5k views
5 votes
Solve for x5(x+4)-3x+3=5

User Kimari
by
6.4k points

1 Answer

7 votes

x=-9

Step-by-step explanation

Step 1

apply the distributive property to eliminate the parenthesis

remember:


a(b+c)=ab+ac

then


\begin{gathered} 5(x+4)-3x+3=5 \\ 5\cdot x+5\cdot4-3x+3=5 \\ 5x+20-3x+3=5 \end{gathered}

Step 2

add similar terms,


\begin{gathered} 5x+20-3x+3=5 \\ (5x-3x)+(20+3)=5 \\ 2x+23=5 \end{gathered}

Step 3

subtract 23 in both sides


\begin{gathered} 2x+23=5 \\ 2x+23-23=5-23 \\ 2x=-18 \end{gathered}

Step 4

finally, divide each side by 2


\begin{gathered} 2x=-18 \\ (2x)/(2)=(-18)/(2) \\ x=-9 \end{gathered}

Hence , the answer is x=-9

User Oba
by
5.9k points